Generative AI adoption among tech-savvy: examining moderated mediated model of knowledge sharing - Zamrudi, Zakky; Wicaksono, Teguh; Mardiana, Mardiana; Khuzaini, Khuzaini; Lihu, Decky C. K. (Manajemen dan Bisnis, 2025)
This study investigates factors influencing AI adoption in education, focusing on the roles of Digital Touchpoints, Tech Savvy, and knowledge-sharing practices among students and instructors. Using an explanatory quantitative design, data were collected from 213 business students through a digital survey. The model measures Digital Touchpoints, Tech Savvy, Gen. AI Adoption, Instructor KS, and Student KS, with a 7-point Likert scale used for responses. Data analysis involved descriptive statistics and PLS-SEM for model evaluation and hypothesis testing. The results show that Digital Touchpoints positively impact both Gen. AI Adoption and Tech Savvy, with Tech Savvy further enhancing AI adoption. Student KS significantly moderates the Digital Touchpoints-Tech Savvy relationship, whereas Instructor KS does not. Mediation analysis reveals that Tech Savvy mediates the effect of Digital Touchpoints on Gen. AI Adoption, though mediated moderation effects are not significant. These findings underscore the importance of digital engagement and peer interactions in promoting tech skills and AI adoption in educational settings.